2008
DOI: 10.1159/000153433
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Clinical Relevance of Segmental Analysis Based on Intelligibility Assessment

Abstract: Objective: In persons with a speech pathology, improved intelligibility is the fundamental goal of treatment. Identification of specific phonetic features that affect intelligibility, contributes to selecting intervention targets. The main purpose of this study was to investigate whether a segmental analysis based on a perceptual phoneme intelligibility assessment is reliable and can be used for target selection. Secondly, the hypothesis that the degree of agreement for phoneme identification may depend on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In more detail, these target phonemes were transcribed in the presence of the remaining phonemes of a word (e.g., transcribing target phoneme 'n' in 'nit' which was presented as '.it'). All three criterion measures were shown to be reliable and valid (Van Nuffelen et al, 2008;Xue et al, 2021b).…”
Section: Discussionmentioning
confidence: 93%
“…In more detail, these target phonemes were transcribed in the presence of the remaining phonemes of a word (e.g., transcribing target phoneme 'n' in 'nit' which was presented as '.it'). All three criterion measures were shown to be reliable and valid (Van Nuffelen et al, 2008;Xue et al, 2021b).…”
Section: Discussionmentioning
confidence: 93%
“…The perceptual intelligibility score is calculated as the percentage of correctly identified phonemes. Previous research [4,15] has demonstrated that the intelligibility scores derived from the DIA are highly reliable (an interrater correlation of 0.91 and an intrarater correlation of 0.93 [15]).…”
Section: Perceptual Test and Evaluation Databasementioning
confidence: 99%
“…The perceptual intelligibility score is calculated as the percentage of correctly identified phonemes. Previous research [2,6] showed that the intelligibility scores derived from the DIA are highly reliable (an intraclass correlation of 0.93 and an interclass correlation of 0.91 [6]).…”
Section: Subjective Evaluation and Databasementioning
confidence: 99%